Relato de casos: recém-nascidos com icterícia neonatal submetidos à exsanguíneotransfusão - LOPES, Jayme Krisney Borges (2020)
Approximately 98% of newborns (NBs) have high levels of bilirubin during the first week after birth, which most often refers to an adaptation of the body to bilibirubin. However, when serum levels are higher than 5mg / dl, it becomes clinically jaundiced, affecting 60% of newborns born at full term and 80% of premature newborns, which shows the relevance of the recognition of sinuses and symptoms, as well as all treatments applicable to treatment to avoid the most acute phase of the change called bilirubin encephalopathy or kernicterus characterized by the high concentration of bilirubin in the blood and its deposition in the tissues of the basal ganglia. Objectives: To describe a series of four cases of jaundiced neonates submitted Methodology: A descriptive, multiple-case, retrospective, documentary, case study study evaluating the impacts on total bilirubin and fractions after hemotherapy. The data were obtained after approval of the Research Ethics Committee of the Institution, from March to April 2018, through a data collection instrument that guided the analysis of the records of the multiprofessional team in the patients' records and in the results of the examinations of total bilibirubin and fractions (BTF) performed during treatment. Results: the maternal profile presented a mean age of 22 years. Blood type A + was present in three cases. All born through normal delivery and coming from the interior of the state. The mean gestational age among the newborns was 37 weeks and the weight of 3121 grams. Three neonates of the four studied were male. All participants completed the fifth minute of life with good vitality. The treatment employed showed a high degree of efficiency and the analysis of the registries allowed to carry out the survey of the profile of the newborns submitted to exchange transfusion in the FSCMPA. Three neonates with type A + blood (75%) and one case with blood type 0+ (25%). The mean postnatal age at which exchange transfusion was performed was 04 days. The laboratory profile of Total Bilirubin and Fractions (BTF) tests before and after exsanguineotransfusion showed a satisfactory impact of hemotherapy, with a mean reduction of up to 44.7% of BTF. Conclusion: Hyperbilirubinemia is a frequent reason for rehospitalization in the public service, although it is easy to treat as evidenced in previous studies. Exchange transfusion was an effective therapy for the reduction of bilirubin levels in the worsening of neonatal jaundice, all occurring within the indications established by the Ministry of Health